Factors important for women who breastfeed in public: a content analysis of review data from FeedFinder. Issue 10 (24th October 2016) - Simpson, Emma; Garbett, Andrew; Comber, Rob; Balaam, Madeline
Abstract : Objective: To examine how the breastfeeding experience is represented by users of FeedFinder (a mobile phone application for finding, reviewing and sharing places to breastfeed in public). Design: Content analysis using FeedFinder database. Setting: FeedFinder, UK, September 2013–June 2015. Methods: Reviews obtained through FeedFinder over a period of 21 months were systematically coded using a conventional content analysis approach, average review scores were calculated for the rating criteria in FeedFinder (comfort, hygiene, privacy, baby facilities) and review texts were analysed for sentiment. We used data from Foursquare to describe the type of venues visited and cross-referenced the location of venues with the Indices of Multiple Deprivation. Results: A total of 1757 reviews were analysed. Of all the reviews obtained, 80% of those were classified as positive, 15.4% were classified as neutral and 4.3% were classified as negative. Important factors that were discussed by women include facilities, service, level of privacy available and qualities of a venue. The majority of venues were classified as cafes (26.4%), shops (24.4%) and pubs (13.4%). Data on IMD were available for 1229 venues mapped within FeedFinder, 23% were located within the most deprived quintile and 16% were located in the least deprived quintile. Conclusions: Women create content that is positive and informative when describing their breastfeeding experience in public. Public health bodies and business owners have the potential to use the data from FeedFinder to impact on service provision. Further work is needed to explore the demographic differences that may help to tailor public health interventions aimed at increasing breastfeeding rates in the UK.